1986
DOI: 10.1152/ajpheart.1986.251.6.h1232
|View full text |Cite
|
Sign up to set email alerts
|

Aminophylline and interstitial adenosine during sustained exercise hyperemia

Abstract: We tested the hypothesis that an increase in interstitial fluid (ISF) adenosine concentration contributes to vasodilation of high oxidative skeletal muscle during sustained free-flow exercise. Canine calf muscles were stimulated at 3 Hz for 10 min before and after the infusion of the adenosine receptor antagonist aminophylline (10 mg/kg). The vasodilation that occurred during aminophylline infusion was allowed to decay before the postaminophylline exercise period was begun. This dose of aminophylline shifted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…However, the same group determined that adenosine could contribute to around 40% of the hyperaemia observed in the later stages of exercise (Ballard et al 1987). The use of the adenosine receptor antagonist theophylline (aminophylline) has also produced equivocal results (Mohrman & Heller, 1984;Proctor, 1984;Thompson, Gorman & Sparks, 1986). Theophylline, although possessing adenosine receptor antagonist properties (pA2 = 5, Collis & Pettinger, 1982), is not an ideal compound to use since it is also able to inhibit cyclic AMP phosphodiesterase activity (Persson, Erjefalt & Karlsson, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…However, the same group determined that adenosine could contribute to around 40% of the hyperaemia observed in the later stages of exercise (Ballard et al 1987). The use of the adenosine receptor antagonist theophylline (aminophylline) has also produced equivocal results (Mohrman & Heller, 1984;Proctor, 1984;Thompson, Gorman & Sparks, 1986). Theophylline, although possessing adenosine receptor antagonist properties (pA2 = 5, Collis & Pettinger, 1982), is not an ideal compound to use since it is also able to inhibit cyclic AMP phosphodiesterase activity (Persson, Erjefalt & Karlsson, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that adenosine is indeed a powerful vasodilator substance (Haddy et al 1967;Granger et al 1978;Berne et al 1983;Lautt and Legare 1985;Eintrei and Calsson 1986;Dobson et al 1986;Thompson et al 1986). Acetate is known to be metabolized into acetyl CoA with the generation of adenosine monophssphate (5'-AMP) from ATP (Liang and Lowenstein 1978;Puig and Fox 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Several of these investigators suggested that their inability to identify an important role for adenosine may be attributed to inadequate blockade of endogenously released adenosine, despite demonstration of effective blockade to exogenously administered adenosine (Honig & Frierson, 1980;Mohrman & Heller, 1984;Thompson et al 1986). Whatever the source of endogenous adenosine (skeletal muscle, neuronally released purines, other), the possible sites of adenosine's action include a direct vasodilatory effect on vascular smooth muscle mediated by the A2 subtype of the Pl-purinergic receptor, and inhibition of noradrenaline release from sympathetic nerve terminals by binding to presynaptic A1-purinergic receptors (Verhaege, Vanhoutte & Shepherd, 1977;Bruns, Lu & Pugsley, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies during free-flow exercise have failed to identify a role for adenosine in the hyperaemic response (Phair & Sparks, 1979;Hester, Guyton & Barber, 1982;Mohrman & Heller, 1984; Klabunde, 1986; Thompson, Gorman & Sparks, 1986; Klabunde, Laughlin, & Armstrong, 1988), but the results of two studies support the hypothesis that adenosine is at least partially involved in the hyperaemia associated with skeletal muscle activity (Proctor & Duling, 1982; Steffen, McKenzie, Bockman & Haddy, 1983). Fuchs, Gorman & Sparks (1986) demonstrated that there was an increased release of adenosine into the venous plasma during free-flow exercise in isolated, perfused dog calf muscles, but they did not find a correlation between adenosine release and exercise blood flow.…”
Section: Introductionmentioning
confidence: 99%